2016
DOI: 10.1007/s12199-016-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical effects of internal contamination with actinides: further controversy on depleted uranium and radioactive warfare

Abstract: The Nuclear Age began in 1945 with testing in New Mexico, USA, and the subsequent bombings of Hiroshima and Nagasaki. Regardless of attempts to limit the development of nuclear weapons, the current world arsenal has reached the staggering dimensions and presents a significant concern for the biosphere and mankind. In an explosion of a nuclear weapon, over 400 radioactive isotopes are released into the biosphere, 40 of which pose potential dangers including iodine, cesium, alkaline earths, and actinides. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…Despite of extensive safety features, inadvertent release of actinides in the working environment remains a global concern as it poses significant health risks to the working personnel. Apart from nuclear facilities, one also cannot rule out the possibilities of actinides being used in the radiological dispersal devices (RDD) . After internal uptake, actinide ions distribute in different organs based on the route of intake and damage the associated tissues by high energy α particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of extensive safety features, inadvertent release of actinides in the working environment remains a global concern as it poses significant health risks to the working personnel. Apart from nuclear facilities, one also cannot rule out the possibilities of actinides being used in the radiological dispersal devices (RDD) . After internal uptake, actinide ions distribute in different organs based on the route of intake and damage the associated tissues by high energy α particles.…”
Section: Introductionmentioning
confidence: 99%
“…After internal uptake, actinide ions distribute in different organs based on the route of intake and damage the associated tissues by high energy α particles. Significant radiation exposures to the organs may also lead to the acute radiation syndrome …”
Section: Introductionmentioning
confidence: 99%
“…У другим студијама Милер и други доказали су да ОУ има утицај и на развој леукемије (Miller, Bonait-Pellie, Merlot, 2005), као и да излагање ОУ in vitro за последицу има геномску нестабилност манифестовану као одгођено репродуктивно одумирање и стварање микронуклеуса (Miller et al, 2003). У свом прегледном раду, Дураковић је приказао истраживања којима је доказана генотокисчност ОУ у еритропоетском и репродуктивном систему, као и тетрагенетски ефекти са мутагенезом и хромозомским аберацијама (Duraković, 2016). Он је истакао да су ефетки ОУ на људе соматски и генетички "са капацитетом промене ћелијске структуре и функције у распону од морфолошких преко трансгенерацијских генетских последица" (Duraković, 2016, p. 113 (Williams, 2007).…”
Section: резултати истраживања последице оу -истраживања In Vitro и In Vivounclassified
“…In their other studies, Miller et al confirmed that DU was also a factor in the development of leukaemia (Miller, Bonait-Pellie, Merlot, 2005) and that DU exposure in vitro results in genomic instability manifested as delayed reproductive death and micronuclei formation (Miller et al, 2003). In his review article, Duraković cited studies which demonstrated DU genotoxicity in the erythropoietic and reproductive systems and DU teratogenic effects with mutagenesis and chromosomal aberrations (Duraković, 2016). He pointed out that the effects of DU on humans are somatic and genetic "with the capacity of alteration of cellular structure and function ranging from morphological through transgenerational genetic effects" (Duraković, 2016, p. 113).…”
Section: Effects Of Du -Studies In Vitro and Studies In Vivomentioning
confidence: 99%
“…Despite the importance of having nuclear power plants to meet the required energy worldwide, nuclear accidents still can happen. During nuclear accidents, a large amount of hazardous, radioactive materials may be released into the environment, including cesium-137 ( 137 C), strontium-90 ( 90 Sr), and uranium-234/235/238 ( 234/235/238 U) [7]. Humans can be exposed to radioactive materials externally when radionuclides stay outside the body or internally through inhalation or ingestion of contaminated air and food, respectively [8].…”
Section: List Of Abbreviationsmentioning
confidence: 99%